Binomial Identity of Luxury Brands: The Role of Consumer Situational Scepticism - Teah, Jun-Huan (Kevin) (Curtin University, 2022)
The purpose of this study is to examine how perceived corporate social responsibility (CSR) motives may influence consumer situational scepticism towards luxury brands and its effects on brand resonance, resilience to negative information and consumer advocacy of luxury brands. The moderating role of perceived fit, commitment, and principle-based entities towards luxury brand CSR initiatives is also investigated.